Implementation of Tri Nga in Culinary MSMEs: A Solution to Overcome Demand Fluctuations and Technology Limitations: inggris - Andriana, Devi; Setianingrum, Diah Ayu; Syaoky Wahidun Ramadhan; Shelomitha Azzahra Ade Putri; Johan Deorian Kurniawan; Ignatius Soni Kurniawan (IJCS: International Journal of Community Service, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are important contributors to the Indonesian economy, but MSME players themselves often have difficulty understanding the problems they face, what they feel, and the solutions. Focusing on the problems of managing fluctuating demand and limitations in technology adoption, this community service program aims to address these issues through the implementation of Tri Nga-a concept developed by Ki Hadjar Dewantara, which emphasizes the processes of Ngerti (understanding), Ngrasa (appreciating), and Nglakoni (doing). The partner chosen in this program is Dapoerangell, a culinary MSME in Yogyakarta that faces constraints in workforce management and lack of technology utilization. Through observation, analysis, and direct engagement with the Participatory Learning and Action (PLA) method, the Tri Nga concept was applied to help partners identify core problems, understand their impact, and implement appropriate solutions. This approach enabled Dapoerangell to develop flexible work systems and plan for the adoption of production technologies to improve operational efficiency. The results of this program show that the application of Tri Nga can encourage sustainable problem solving and empower MSMEs to independently manage future challenges. The outputs of this activity have been published online as a medium to share practical insights to other MSMEs facing similar challenges